KAJIAN PERMASALAHAN JALUR HIJAU KOTA YOGYAKARTA UNTUK PENGEMBANGAN LANSKAP HUTAN KOTA DAN URBAN GREENWAYS (ANALYSIS ON YOGYAKARTA STREET GREENING FOR DEVELOPMENT OF URBAN FOREST LANDSCAPE AND URBAN GREENWAYS) - Irwan, Sri Nurul Rofiqo (Ikatan Arsitek Lanskap Indonesia, 2012)
Urban area has been getting hotter due to global warming phenomenon. Urban green space quality was enhanced by improving the functions of urban green space that created cooling effect and comfort. The purposes of the study were to observe actual green space problems, to develop green space functions by urban forest landscape dan urban greenways in Yogyakarta City. Development of urban forest landscape that imitate the structure of tropical rain forest and urban greenway as green corridor of sustainable city, covered optimally the green space functions and biodiversity conservation in urban areas. Observations at some locations of Yogyakarta green space showed various field problems. Tree cultivation techniques, maintenance, tree functions have not been in guideline of the conceptual landscape techniques and planning. Investigation on tree canopy coverage in the central city of Yogyakarta, Malioboro and Kota Baru Areas, showed a significant different effect on comfort activity by analysis on tree canopy coverage. Kota Baru residence presented 64-84% canopy coverage with the dominance of Tanjung Tree (Mimusops elengi) and Beringin Tree (Ficus benjamina). The business area of Malioboro showed 57-60% canopy coverage with the dominance of Angsana Tree (Ptericarpus indicus) and Asam Tree (Tamarindus indica). This difference of canopy coverage indicated Kota Baru area was more comfortable than Malioboro area. The concept of development of urban green space proceeds to the development of urban forest landscape for connectivity of urban greenways by improving the conservation of biodiversity and focusing the application of vegetation functions in Yogyakarta Green Space.